The pernicious institution of the party-appointed arbitrator - Hans Smit (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
As arbitration has grown by leaps and bounds, so has the role of the party-appointed arbitrator. Surprisingly, this has not led to increased inquiry into the appropriateness of having arbitrators appointed by the parties in general, or in arbitrations against states in particular.
Keywords: 330